Strategic Brand Management Components for Thai SMEs: Empirical Evidence from Exploratory Factor Analysis - คำขันแก้ว พงศ์ศิริ (Parichart Journal, 2017)
This research aims to analyze the strategic brand management component of Thai SMEs. In total 933 respondents were Thai SMEs in manufacturing and service sector, which registered as a member of the office of SMEs promotion. The questionnaire was the research instrument. The confirmatory factor analysis was applied to analyze the data. The coefficient reliability of questionnaire was 0.927. The five strategic brand management components of Thai SMEs consist of context analysis, strategic brand designing, strategic brand building, strategic brand implementing and continuously strategic brand building. The result of confirmatory factor analysis presented that the ensured model fitted the empirical data. The Goodness-of-fit index of revised model indicate sufficient fit in that Chi-square statistic = 337.39, df = 73, p-value = 0.41, GFI = 0.997, AGFI = 0.981, CFI = 0.999 RMSEA = 0.047.